Copper(I) bromide-catalyzed carbonylative coupling of aryl halides with phenols, alcohols and amines using sodium cyanide as C-1 source: a synthesis of carboxylic acid derivatives - Prasad, Pragati K.; Sudalai, Arumugam (Advanced Synthesis & Catalysis, 2014)
A new ``carbon monoxide-free'' synthesis of carboxylate derivatives via carbonylative coupling of aryl bromides with phenols, alcohols, amines and acids in the presence of copper(I) bromide as catalyst and sodium cyanide in a stoichiometric amount has been developed. Its intramolecular version provides for the preparation of lactones (e.g., isochroman-1-ones and isobenzfuranones), imides, anhydrides and lactams in excellent yields (73-96%).
Keywords: anhydrides; C-1 building blocks; isochroman-1-ones; lactams; lactones